EUS guided gallbladder drainage - Posner, Hannah; Widmer, Jessica (Translational Gastroenterology and Hepatology; Vol 5 (July 2020): Translational Gastroenterology and Hepatology, 2020)
Cholecystectomy is the gold standard treatment for acute cholecystitis, but it may not be appropriate for patients with significant comorbidities. Percutaneous gallbladder drainage (PT-GBD) and endoscopic transpapillary gallbladder drainage (ET-GBD) are alternatives with good technical and clinical success rates, but are limited by technical challenges and the need for definitive therapy. EUS- guided gallbladder drainage (EUS-GBD) is quickly becoming the preferred modality of treatment at expert centers in this cohort of patients due to increased efficacy and minimal adverse events. Technicalities of the procedure, including selection of access site, should be informed by the ultimate needs and anatomy of each patient. With the evolution of new stents and accessories, including a cautery-enhanced lumen apposing metal stent deployment system, success rates and adverse events are favorable. A review of published case series demonstrates an overall clinical success rate of approximately 97% for EUS-GBD. The most common complication is pneumoperitoneum, so the evolution of self-expanding LAMS is promising. EUS-GBD has been successfully described in cases where definitive therapy or a bridge to cholecystectomy is needed. As the procedure’s applications continue to evolve, there should be greater discussion about specific details including access site and stent selection.